Impact of Wood Biochar and Its Interactions with Mycorrhizal Fungi, Phosphorus Fertilization and Irrigation Strategies on Potato Growth. (11th August 2016) - Liu, C.; Liu, F.; Ravnskov, S.; Rubæk, G. H.; Sun, Z.; Andersen, M. N.
Abstract: Biochar amendment to soil has the potential to improve soil quality and increase crop yield. Arbuscular mycorrhizal fungi (AMF) provide beneficial plant services of stress alleviation with respect to phosphorus (P) deficiency and drought. The aim of this study was to explore interactive effects of biochar with AMF, P fertilization levels and irrigation strategies on growth of potato plants. Potato plants were amended with wood biochar of 0.74 % w/w (B+) or not (B−), fertilized with phosphorus of 0.11 mg P g −1 soil (P1) or not (P0), irrigated with full irrigation (FI) or partial root‐zone drying irrigation (PRD) and inoculated with AMF of Rhizophagus irregularis (M+) or not (M−) in split‐root pots in a sandy loam soil. Plants were analysed for growth performance, P and nitrogen (N) uptake and water use efficiency (WUE). Biochar adsorption of mineral P and N in aqueous solution was tested in subexperiment. B+ significantly decreased plant biomass production except under P0 FI M−, where B+ increased plant biomass. This growth stimulation was counteracted by treatments of P1, PRD and M+. B+ significantly decreased plant leaf area, P and N uptake and WUE, but had no significant effect on root biomass and soil pH. The positive plant growth response to AMF was substantially reduced by biochar amendment. The wood biochar had no adsorption for mineral N, and it had 0.96 % adsorption for mineral P in aqueous solution. The results suggested that the negative effect of wood biochar application on plant growth may due to the reduced plant uptake of P and N and the possibility of phytotoxic effects of wood biochar on potato growth. It was concluded that the wood biochar used in current study had negative impact on plant growth and P/N uptake and it is not recommendable to apply this wood biochar to mycorrhizal agro‐system, to soil fertilized with high rate of P or to soil suffering water deficiency.